Pengelolaan Hutan Rakyat Oleh Kelompok Pemilik Hutan Rakyat Di Desa Bandar Dalam Kecamatan Sidomulyo Kabupaten Lampung Selatan - Slamet Budi Yuwono; Rudi Hilmanto (Jurnal Sylva Lestari, 2015)
The private forest is one of the alternative solutions to the pressure of forest resources. The benefits to be gained from private forests management includes fulfill the needs of wood, increase public revenues, and increase the productivity of land.Â  The benefit has received by the public depends on the management carried out by private forest owners. The purposes of this study were to determine the social and economic characteristics of people who participate in managing private forests, and to determine the level of private forest management covers all aspects of planning, organizing, actuating, evaluation and monitoring. The research was conducted on August till September 2014 in Bandar Dalam village Sidomulyo District of South Lampung. The numbers of samples were 38 respondents by simple random sampling method. Data analysis methods used qualitative descriptive analysis. The results,were it can be concluded that: (1) the social and economic characteristics of the people who manage private forests mostly included in the productive age work and have a second job, amount of family burden is only a bit, and private forests land that they manage quite extensive so that their income quite high, although most low level of education; and (2) private forest management consisted of the planning aspect in medium category, organizational aspect in medium category, planting implementation aspect in both category, implementation of maintenance aspect in medium category, harvesting implementation aspect in both category, marketing implementation aspect in poor category, and monitoring-evaluation aspect are in medium category. Overall level of private forest management is medium category. Keywords: Private forest, forest management, private forest owners